Financial accounting : international financial reporting standards - Harrison, Walter T. (boston : Pearson, 2011)
Fully revised to include International Financial Reporting Standards throughout, the Global Edition of Financial Accounting helps you understand the key concepts and master the accounting cycle.
1 Conceptual Framework and Financial Statements -- 2 Transaction Analysis -- 3 Accrual Accounting and Income -- 4 Internal Control and Cash -- 5 Short-Term Investments and Receivables -- 6 Inventory and Cost of Goods Sold -- 7 PPE and Intangibles -- 8 Liabilities -- 9 Shareholder$1 (Bs Equity -- 10 Long-Term Investments and International Operations -- 11 The Income Statement and the Statement of Changes in Equity -- 12 Statement of Cash Flows -- 13 Financial Statement Analysis.s
Includes index.
1
Keywords: Accounting